Nitric oxide donors enhanced Ca2+ currents and blocked noradrenaline-induced Ca2+ current inhibition in rat sympathetic neurons. - Chen, C (1995)
1. The effects of NO donors on Ca2+ channel currents and noradrenaline (NA)-induced Ca2+ current inhibition were investigated in superior cervical ganglion (SCG) neurons using the whole-cell patch-clamp technique. 2. A 500 microM concentration of the NO donors, sodium nitroprusside (SNP) and S-nitroso-N-acetylpenicillamine (SNAP), enhanced Ca2+ current amplitude after either extracellular or intracellular application. The magnitude of Ca2+ current enhancement induced by NO donors was greater after intracellular application than after extracellular application. 3. Intracellular application of 1 mM guanosine 3',5'-cyclic monophosphate (cGMP) or 100 microM M&B 22948 (2-O-propoxyphenyl-8-azapurine-6-one), a cGMP phosphodiesterase inhibitor, or extracellular application of 1 mM 8-bromoguanosine 3',5'-cyclic monophosphate (8-Br-cGMP) also increased the amplitude of Ca2+ currents thus mimicking the effect of the NO donors on Ca2+ channels. In contrast, pretreatment with Methylene Blue (100 microM) decreased the SNP (500 microM)-induced enhancement of Ca2+ currents. 4. Intracellular application of 500 microM SNP and SNAP, 100 microM M&B 22948 or 1 mM cGMP, or extracellular application of 200 microM 8-Br-cGMP reduced the magnitude of Ca2+ current inhibition induced by 5 microM NA. In addition, 500 microM SNP prevented the NA-induced shift of tail current activation curves to more depolarized potentials. 5. Internal dialysis with 500 microM SNP and SNAP or 1 mM cGMP, or extracellular application of 200 microM 8-Br-cGMP, reduced Ca2+ current facilitation produced by a depolarizing conditioning pulse both in the absence and presence of 5 microM NA. 6. The results suggest that NO donors induce enhancement of Ca2+ currents and block NA-induced Ca2+ current inhibition of SCG neurons via stimulation of cGMP formation.